2018
DOI: 10.1093/pcp/pcy049
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine- and Amino Acid-Related Metabolism: The Roles of Arginine and Ornithine are Associated with the Embryogenic Potential

Abstract: The mechanisms that control polyamine (PA) metabolism in plant cell lines with different embryogenic potential are not well understood. This study involved the use of two Araucaria angustifolia cell lines, one of which was defined as being blocked, in that the cells were incapable of developing somatic embryos, and the other as being responsive, as the cells could generate somatic embryos. Cellular PA metabolism was modulated by using 5 mM arginine (Arg) or ornithine (Orn) at two time points during cell growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 74 publications
0
26
0
Order By: Relevance
“…The ODC gene has been lost from Arabidopsis thaliana and many members of the Brassicaceae (Hanfrey et al, 2010), indicating that the ornithine pathway is not essential for normal growth. In the third route, Arg is first converted into citrulline (Cit), which is then decarboxylated by citrulline decarboxylase (CDC) to form Put (Han, 2016; Ouyang et al, 2017; De Oliveira et al, 2018). To date, the Cit pathway has only been found in sesame, and so the first two pathways are more common in plants.…”
Section: Distribution and Metabolism Of Pas In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ODC gene has been lost from Arabidopsis thaliana and many members of the Brassicaceae (Hanfrey et al, 2010), indicating that the ornithine pathway is not essential for normal growth. In the third route, Arg is first converted into citrulline (Cit), which is then decarboxylated by citrulline decarboxylase (CDC) to form Put (Han, 2016; Ouyang et al, 2017; De Oliveira et al, 2018). To date, the Cit pathway has only been found in sesame, and so the first two pathways are more common in plants.…”
Section: Distribution and Metabolism Of Pas In Plantsmentioning
confidence: 99%
“…This kind of PA forms the largest pools of PAs in plants (Kusano et al, 2008; Bassard et al, 2010). Many studies have confirmed that PSCC-PAs act as secondary metabolites, and participate not only in the local allergic reaction of plants against external infestation (Kumar et al, 1997), but also in plant morphogenesis (de Oliveira et al, 2016; De Oliveira et al, 2018; Mustafavi et al, 2018).…”
Section: Introductionmentioning
confidence: 95%
“…Polyamine trofiles. The polyamine profiles and content were performed according to a previous study 38 Briefly, serum samples from patients with Leishmaniasis (60 µl) were mixed with cold 5% (v/v) perchloric acid at a ratio of 1:4 (v/v). Then, the samples were submitted to three cycles of freezing (− 20 °C) and thawing (at room temperature), prior to centrifugation at 11,000g for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Dansylated polyamines were resuspended in 100 µl of acetonitrile. Polyamines were separated by high-performance liquid chromatography (HPLC, Shimadzu, Japan) using a C18 reversed-phase column (5 µm × 4.6 mm × 250 mm-Sulpelcosil, Supelco), as described previously 38 . Polyamines were detected at 340 nm (excitation) and 510 nm (emission) wavelengths with an RF-20A fluorescence detector (Shimadzu).…”
Section: Methodsmentioning
confidence: 99%
“…During oxidative stress of plants, polyamines play a complicated role (69). First on, PAs may also enhance the potential of various anti-oxidant enzymes in plants, just so oxidant stress due to diverse environmental factors can actually be controlled.…”
Section: Oxidative Stressesmentioning
confidence: 99%